Использование электрической дуги для получения металлических порошков - Боков, В. М.; Сиса, О. Ф.; Bokov, V.; Sisa, O. (My University, 2019)
Получены и исследованы порошки из титанового сплава ВТЗ-1 и твердого сплава ВК-15, предлагается их промышленное использование, а именно для поверхностного напыления. Предложены высокопроизводительные способы и устройства для получения металлических порошков с использованием электрической дуги в поперечном гидродинамическом потоке рабочей жидкости, которая горит без пауз, позволяющие по сравнению с электроэрозионным диспергированием в насыпном слое повысить производительность диспергирования на порядок и более, а также снизить количество концевых технологических отходов (электродов) в 4-6 раз. Modern methods of electro-erosive dispersion of electrically conductive materials that use non-stationary forms of electrical discharges in fluid have low productivity. That is associated with long pauses of discharges. The objective of this research is to raise the productivity of obtaining metal powders. From a methodological point of view, a metal powder was obtained during in the process of research using an electric arc in the transverse hydrodynamic flow of the working fluid as a product of dispersion of specially prepared work-pieces and as a waste item (electrodes erosion products) of implementing the method of electric-arc treatment of two flat surfaces in the bipolar mode. During the research work, powders from the BT3-1 titanium alloy and the BK-15 hard alloy were obtained and investigated. The proposal was put forward on a possibility of their industrial use, especially for surface spraying. The high-performance methods and appliances were suggested to obtain metal powders using an electric arc in the transverse hydrodynamic flow of the working fluid that burns without a pause. They make it possible to increase dispersion productivity in a fixed-bed layer by an order of magnitude and more as compared with the electro-erosive dispersion, as well as to reduce the number of terminal process waste (i.e. electrodes) by 4 to 6 times.
Use of electric arc for metal powders
Keywords: электрическая дуга; гидродинамический поток; металлический порошок; способы и устройства; electric arc; hydrodynamic flow; metal powder; methods and appliances